JAK inhibitors: A new dawn for oral therapies in inflammatory bowel diseases - Herrera-deGuise, Claudia; Serra-Ruiz, Xavier; Lastiri, Ernesto; Borruel, Natalia (Frontiers in Medicine, 2023)
Inflammatory bowel disease (IBD) is a chronic immune-mediated condition of the gastrointestinal tract that requires chronic treatment and strict surveillance. Development of new monoclonal antibodies targeting one or a few single cytokines, including anti-tumor necrosis factor agents, anti-IL 12/23 inhibitors, and anti-α4β7 integrin inhibitors, have dominated the pharmacological armamentarium in IBD in the last 20 years. Still, many patients experience incomplete or loss of response or develop serious adverse events and drug discontinuation. Janus kinase (JAK) is key to modulating the signal transduction pathway of several proinflammatory cytokines directly involved in gastrointestinal inflammation and, thus, probably IBD pathogenesis. Targeting the JAK-STAT pathway offers excellent potential for the treatment of IBD. The European Medical Agency has approved three JAK inhibitors for treating adults with moderate to severe Ulcerative Colitis when other treatments, including biological agents, have failed or no longer work or if the patient cannot take them. Although there are currently no approved JAK inhibitors for Crohn’s disease, upadacitinib and filgotinib have shown increased remission rates in these patients. Other JAK inhibitors, including gut-selective molecules, are currently being studied IBD. This review will discuss the JAK-STAT pathway, its implication in the pathogenesis of IBD, and the most recent evidence from clinical trials regarding the use of JAK inhibitors and their safety in IBD patients.